Ensaio de citotoxicidade osteoblástica em amostras porosas das ligas Ti-6Al-4V, Ti-13Nb-13Zr, Ti-35Nb, Ti-35Nb-7Zr-5Ta e TiCP - Campos, Gabriela Esteves de [UNESP] (2014)
Cellular and tissue events that occur during osseointegration process are directly influenced by composition, morphology and topography of the biomaterial. Titanium (Ti) and its alloys are commonly used for this purpose, since its elasticity can be controlled by porous topography and the chemical composition of the alloy. The aim of this study was to evaluate the cytotoxicity of Commercially Pure Titanium grade 2 (CPTi), Ti-6Al-4V (Titanium-Aluminum-Vanadium), Ti-13Nb- 13Zr (Titanium-Niobium-Zirconium), Ti-35Nb (Titanium-Niobium) and Ti-35Nb-7Zr-5Ta (Titanium-Niobium- Zirconium -Tantalum) alloys. For each studied alloy, 720 samples in the form of discs were made by powder metallurgy and characterized by means of Spectrophotometry of Dispersive Energy (SDE) and metallographic analysis. Ostegenic cells from the calvaria of newborn rats were cultured on the samples of each group and evaluated according to cell growth (CG) (24 hours, 3 and 10 days), cell viability (CV) (3, 10 and 14 days), total protein content (TP) and alkaline phosphatase activity (ALP) (3 and 10 days), production of TGF- 1, TNF- and IL- 6 (7 and 14 days) and mineralized nodules formation (MN) (14 and 21 days). Data obtained was analysed by statistical ANOVA and Tukey's tests, with 5% significance level. SDE detected the presence of constitutive elements of each alloy. Metallographic analysis showed samples structure with 42% of linked and different-size pores. CG was higher at day 10 for Ti-13Nb-13Zr, with statistical difference. New alloys´ CV were similar to CPTi, with higher averages than Ti- 6Al-4V and statistical difference at days 10 and 14. TP at day 10 showed higher average and statistical difference to Ti-35Nb-7Zr-5Ta. 18 ALP exhibited statistical differente between Ti-6Al-4V (highest average) and CPTi and Ti-35Nb. MN were higher and different statistically at day 14 for Ti-35Nb-7Zr-5Ta e Ti-35Nb and at day 21 for the same plus ....